Exposure–Response Analyses of Asbestos and Lung Cancer Subtypes in a Pooled Analysis of Case–Control Studies. Issue 2 (March 2017) - Olsson, Ann C.; Vermeulen, Roel; Schüz, Joachim; Kromhout, Hans; Pesch, Beate; Peters, Susan; Behrens, Thomas; Portengen, Lützen; Mirabelli, Dario; Gustavsson, Per; Kendzia, Benjamin; Almansa, Josue; et al.
Abstract : Background: Evidence is limited regarding risk and the shape of the exposure–response curve at low asbestos exposure levels. We estimated the exposure–response for occupational asbestos exposure and assessed the joint effect of asbestos exposure and smoking by sex and lung cancer subtype in general population studies. Methods: We pooled 14 case–control studies conducted in 1985–2010 in Europe and Canada, including 17, 705 lung cancer cases and 21, 813 controls with detailed information on tobacco habits and lifetime occupations. We developed a quantitative job-exposure-matrix to estimate job-, time period-, and region-specific exposure levels. Fiber-years (ff/ml-years) were calculated for each subject by linking the matrix with individual occupational histories. We fit unconditional logistic regression models to estimate odds ratios (ORs), 95% confidence intervals (CIs), and trends. Results: The fully adjusted OR for ever-exposure to asbestos was 1.24 (95% CI, 1.18, 1.31) in men and 1.12 (95% CI, 0.95, 1.31) in women. In men, increasing lung cancer risk was observed with increasing exposure in all smoking categories and for all three major lung cancer subtypes. In women, lung cancer risk for all subtypes was increased in current smokers (ORs ~two-fold). The joint effect of asbestos exposure and smoking did not deviate from multiplicativity among men, and was more than additive among women. Conclusions: Our results in men showed an excess risk of lung cancer and its subtypes at low cumulative exposure levels, with a steeper exposure–response slope in this exposure range than at higher, previously studied levels. (See video abstract at, http://links.lww.com/EDE/B161 .) Abstract : Supplemental Digital Content is available in the text.